(3fjd GdbQHGJ dCgd GdYbHGJs - (3YHO GdSdGe Hf GdWjH Hf eMeO GdbGOQj GdMSfj GdeZQHj GdaGSj, CHh eMeO,J (B1110 (3g` s
(3ChdgG (B:s
(3MeOkG def CSYO Cgd GdYbHI HfUQI GdOjf GdYdi efbHg s
(3BNQgG (B:s
(3Ke GdUdGI hGdSdGe GdTGai Ydi GdQShd GdcGed GdChUGa hGdBd hGdUMH Chdj GdhaGA eG RGd aVd Gddg Ph GdQLGA s
(3Vef eLehY , JQJjHgG (B: (3ef U (B119 - (3U(B122s
(3efXheIs
(3ofbdJ ef NW eDdagGs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B5 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B225s
Keywords: (3GdJGQjNs